2021
DOI: 10.1007/s40119-021-00231-9
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke and Sleep: The Linking Genetic Factors

Abstract: This review summarizes the available data about genetic factors which can link ischemic stroke and sleep. Sleep patterns (subjective and objective measures) are characterized by heritability and comprise up to 38-46%. According to Mendelian randomization analysis, genetic liability for short sleep duration and frequent insomnia symptoms is associated with ischemic stroke (predominantly of large artery subtype). The potential genetic links include variants of circadian genes, genes encoding components of neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 209 publications
(241 reference statements)
0
9
0
Order By: Relevance
“…For example, the mother's age and education level affected infant mortality ( 6 ). Many diseases, such as cardiovascular disease, diabetes and malignant tumors, are related to bad living habits and sleeping habits ( 7 9 ). Secondly, personal social networks also significantly affect personal health.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mother's age and education level affected infant mortality ( 6 ). Many diseases, such as cardiovascular disease, diabetes and malignant tumors, are related to bad living habits and sleeping habits ( 7 9 ). Secondly, personal social networks also significantly affect personal health.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Besides, a Mendelian randomization analysis showed that short sleep duration and frequent insomnia symptoms are associated with a subtype of ischemic stroke. 30 Sleep deprivation may increase HDAC expression in the hippocampus, adversely affecting structural and functional synaptic plasticity and memory formation, leading to spatial memory decline, which could be reversed by HDAC inhibition. 31 Therefore, we hypothesized that HDAC9 is functionally involved in migraine and insomnia through the dysregulation of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian system influences several cardiovascular risk factors, such as circulating catecholamine levels, blood pressure, heart rate, vagal modulation, platelet aggregability, and immune responses, thus having a possible impact on stroke risk [106]. Several circadian gene polymorphisms and haplotypes have been investigated as potential genetic risk factors of stroke [107]. Genes associated with a protective role against stroke were a single-nucleotide polymorphism of CLOCK gene [108] and PER1 and PER2 genes [109].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Genes associated with a protective role against stroke were a single-nucleotide polymorphism of CLOCK gene [108] and PER1 and PER2 genes [109]. Genome-wide association studies demonstrated an association between genetic variants of melatonin receptors 2 and the risk of metabolic disorders, such as type 2 diabetes mellitus and insulin resistance, which may in turn increase the risk of stroke [107].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation